Study of anti-inflammatory, antioxidant, antimicrobial and mineralizing effects of an N-isopropenylimidazole zinc metal complex derivative in experimental endodontic-periodontal lesions in rats - Pavel A. Galenko-Yaroshevsky; Ivan I. Pavlyuchenko; Olga V. Shelemekh; Boris A. Trofimov; Lidiya N. Parshina; Viktor L. Popkov; Svetlana A. Demyanenko; Oleg V. Tsymbalov; Andrey V. Zadorozhniy; Anait V. Zelenskaya; Irina B. Nektarevskaya; Alina V. Sergeeva; et al. (Research Results in Pharmacology)
Introduction: The combination treatment of patients with dentition problems including endodontic-periodontal lesions (EPL) is known to widely involve anti-inflammatory drugs, including non-steroidal anti-inflammatory agents, and antimicrobial drugs, in particular antibiotics and antiseptics, from which the former often lead to the development of gastro- and neuropathy, lesions of kidneys and liver, as well as the cardiovascular system, and the latter, in addition to serious side effects, lead to the development of steady resistance of pathogenic microorganisms and dysbacteriosis. This necessitates search for and development of new molecules with a wide range of therapeutic effects aimed to block the infectious and inflammatory process and to restore the functional ability of teeth in EPLs as much as possible (depending on a lesion severity). The aim of the study was to examine the anti-inflammatory, antioxidant, antimicrobial and mineralizing effects of an N-isopropenylimidazole zinc metal complex derivative in experimental endodontic-periodontal lesions in rats.